2020
DOI: 10.3390/ijerph17020491
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chemotherapy, Laparoscopy, and Cytology on Stage IC Ovarian Clear Cell Carcinoma: A Long-Term, Single-Center Study

Abstract: Ovarian clear cell carcinoma (OCCC) is the second common histology of epithelial ovarian cancer in Taiwan. Stage IC is common, especially during minimally invasive surgery. Adjuvant chemotherapy in stage IC OCCC is unavoidable, and paclitaxel-based chemotherapy in Taiwan is self-paid. However, surgical spillage from minimally invasive surgery as a cause of unfavorable prognosis is still uncertain. The information of patients with stage IC OCCC, corresponding to a period of January 1995 to December 2016, was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 8 publications
3
9
0
Order By: Relevance
“…It was reported that the response rate of OCCC to conventional platinum was much lower than serous type in the first-line setting [19]. Published studies mainly focused on the performance of chemotherapy on early-stage cases [20][21][22]. In our study, we noted that chemotherapy was significantly associated with OS and CSS, implying its value in improving survival outcomes.…”
Section: Discussionsupporting
confidence: 53%
“…It was reported that the response rate of OCCC to conventional platinum was much lower than serous type in the first-line setting [19]. Published studies mainly focused on the performance of chemotherapy on early-stage cases [20][21][22]. In our study, we noted that chemotherapy was significantly associated with OS and CSS, implying its value in improving survival outcomes.…”
Section: Discussionsupporting
confidence: 53%
“…It was reported that the response rate of OCCC to conventional platinum was much lower than serous type in the rst-line setting [19]. Published studies mainly focused on the performance of chemotherapy on early-stage cases [20][21][22]. In our study, chemotherapy was signi cantly associated with OS and CSS, implying its value in improving survival outcomes.…”
Section: Discussionsupporting
confidence: 51%
“…It was reported that the response rate of OCCC to conventional platinum was much lower than serous type in the rst-line setting [19]. Published studies mainly focused on the performance of chemotherapy on early-stage cases [20][21][22]. In our study, we noted that chemotherapy was signi cantly associated with OS and CSS, implying its value in improving survival outcomes.…”
Section: Discussionsupporting
confidence: 51%